2020
DOI: 10.1071/py19181
|View full text |Cite
|
Sign up to set email alerts
|

From participation to diagnostic assessment: a systematic scoping review of the role of the primary healthcare sector in the National Bowel Cancer Screening Program

Abstract: Primary health care (PHC) plays a vital support role in organised colorectal cancer (CRC) screening programs by encouraging patient participation and ensuring timely referral for diagnostic assessment follow up. A systematic scoping review of the current evidence was conducted to inform strategies that better engage the PHC sector in organised CRC screening programs. Articles published from 2005 to November 2019 were searched across five databases. Evidence was synthesised and interventions that specifically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…We undertook a cross-sectional web-based survey, informed by a recent systematic scoping review (Holden et al, 2020), to explore individual, practice and contextual factors that might influence screening recommendations in Australian general practice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We undertook a cross-sectional web-based survey, informed by a recent systematic scoping review (Holden et al, 2020), to explore individual, practice and contextual factors that might influence screening recommendations in Australian general practice.…”
Section: Methodsmentioning
confidence: 99%
“…A three-level (patient, organisation and environmental) complexity framework of contextual factors, modified from Lau et al (Lau et al, 2016), was applied with selected factors identified from the literature (Holden et al, 2020):…”
Section: Study Factorsmentioning
confidence: 99%
“…Our recent systematic review found that interventions that were part of a quality improvement (QI) process maximised use of GPs' influence in recommending CRC screening participation, particularly for underscreened or never-screened patients. 6 However, the variation in reporting means that it is unclear which QI elements contribute to the overall study outcomes. 6 Based on our review and a general practice survey 10 , we developed a multicomponent CRC-QI intervention comprising eight elements to support delivery of the NBCSP in general practice ( Table 1).…”
mentioning
confidence: 99%
“…6 However, the variation in reporting means that it is unclear which QI elements contribute to the overall study outcomes. 6 Based on our review and a general practice survey 10 , we developed a multicomponent CRC-QI intervention comprising eight elements to support delivery of the NBCSP in general practice ( Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation